A tomada de decisão de gestores da atenção secundária à saúde - Simone Graziele Silva Cunha (2016)
The daily management work is characterized by decisions taken in different institutional settings and influence the work of professionals of different categories. The managers work have external variables, such as laws and regulations, which in some situations are not in line with the users needs, service interruption, network fragmentation, insufficient and / or inadequate resources and overcrowding. Also highlighted are internal variables, among which may be mentioned the staff turnover increase, inadequate profile management team and professional body and the deficiency of communication and information. By the exposed it inquires: How do Immediate Care Units (IAU) managers experience decision-making in daily work? This study aimed to: Understand the experience of managers in decision-making in the Immediate PSCs context. This is a single case study of a qualitative nature, developed in UAI, located in the city of Betim, Minas Gerais. Participants were managers and coordinators of UAI and health secretaries. Data were collected through interviews with semi-structured script, complementing the interview technique it was used the "Gibi" and observation. We conducted content analysis proposed by Bardin (2011). The project was approved by the Ethics Committee on Human Research of the Federal University of Minas Gerais (COEP / UFMG) (Opinion No. 1,174,603), according to Resolution 466 of 2012 of the National Health Council. Respondents filled out and signed the Consent and Informed Term (WIC). Through the data analysis the management profile was produced and three thematic categories were built, which are: "Activities of the daily work of managers in UAI," "process and elements of the management decision-making in UAI," "Facilities and barriers in managers decision making of UAI ". This research has identified that the managers daily work is permeated by factors that directly affect the daily routines of work. Managers, nursing coordinators and medical coordinators are the key players in decision-making in UAI. Moreover, it was possible to identify which managers develop strategies and actions to make decisions through steps such as checking the problem, listen to those involved, evaluate the arguments, analyze the facts by identifying data and information, document proposed and discuss them, choosing priorities, measure the consequences of decisions and ultimately implement the action that will best solve the problem. Knowing the professionals, good relationship with the work team and active communication are factors that contribute to decision making, in addition, knowledge of the staff rules and regulations of the institution is essential. As complicating factors were highlighted lack and inefficiency of the information system, shortage of physical resources, problems in the financial management of the municipality, political influence and shortcomings mainly in people management. It concludes that managers have a common goal in decision making. These objectives are to improve, simplify and organize processes that result in improvements at work and, especially, the pursuit for user satisfaction.